Research on the Manufacturing Process of Steel Bridge Piers for Suspended Monorail Transit - YIN Guifang; GONG Wenqiang; CHEN Xiaoshan; KONG Haiyong; WEI Chao; ZHU Gang (Chengshi guidao jiaotong yanjiu)
［Objective］ Manufacturing accuracy of the steel bridge pier, which is an important part of the suspended monorail transit system, determines the erection and installation of track beams, thereby affecting the train smooth running. Therefore, it is necessary to conduct research on it. ［Method］ Based on the Tourism Special Line Phase I Project, a supporting facility for Wuhan Optics Valley Ecological Corridor Tourism, the process research is conducted in response to the T-shaped structural characteristics of steel bridge piers for suspended monorail transit and combining the design requirements for the manufacturing accuracy of steel bridge piers. The difficulties in the manufacturing process of monorail steel bridge piers are analyzed, and the manufacturing schemes for the steel cap beams are compared and selected. Moreover, the manufacturing process and accuracy control methods of suspended monorail steel bridge piers are systematically expounded. ［Result & Conclusion］ Through the actual manufacturing of steel bridge piers and the on-site erection and installation of track beams, the distance between the lug plates of the steel cap beams (0-2 mm) and the distance from the cantilever center to the column central line (-2-2 mm) can be effectively controlled. After the overall assembly and formation of the steel bridge piers, the distance error between the line connecting the positioning point of the left cap beam pin axis to the center point at the steel column bottom, and the line connecting the positioning point of the right cap beam pin axis to the center point at the steel column bottom is ≤3 mm, and the elevation error between the center of the lug plate and the center of the column is ≤2 mm, meeting the requirements for the overall assembly and production of steel bridge piers, and realizing the control over the manufacturing accuracy of steel bridge piers.